Italian Household Demand : Monetary Assets and Government Debt. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
The composition of Italian household wealth has undergone significant changes in the last decade, partly reflecting the growth of public debt and monetary policies aimed at encouraging its absorption by the household sector. Within a theoretical framework consistent with the 'money in the utility function' approach, this paper investigates household preferences for liquidity services provided by short-term financial assets. In the attempt to explain the factors underlying those changes, the empirical analysis provides information on the pattern of substitution for the main components of financial wealth and permits analysis of a variety of government interventions in asset markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet